Identifikasi Modal Sosial dalam Penjualan Ternak Domba pada Kelompok Peternak Domba Bina Mandiri di Desa Sidomlyo Kecamatan Silo Kabupaten Jember - Nur Fauziyatul Khairiyah; - Riniati; Endah Kurnia Lestari (MediaTrend, 2020)
This research aims to identify social capital in the sale of sheep livestock in the Bina Mandiri Sheep Farmers Group in Sidomulyo Village, Silo District, Jember Regency. The sale of sheep livestock changes when production activities are carried out collectively or in groups. Therefore, this study seeks to describe the condition of social capital found in the Bina Mandiri Sheep Farmers Group. The components of social capital used are trust, networks and values and norms. This research is a qualitative descriptive study that uses the method of in-depth interviews with key informants and additional informants. Testing the validity of the data in this study using triangulation techniques. Network and Trust are the main elements in the group that can increase the sale of sheep. The existence of trust is able to form a network that can expand the scale of business. Elements of values and norms in the group complement the network elements and trust that the sale of sheep can be increased. So, it can be concluded that the results of this study indicate the condition of social capital in the Bina Mandiri Sheep Farmer Group has a role in the sale of sheep. Keywords : Network, Norms, Trust, Sale of Sheep